Developing Impact Investment Opportunities for Return-Seeking Capital in Sustainable Marine Capture Fisheries - Inamdar, Neel (World Bank, Washington, DC, 2019)
The Food and Agriculture Organization (FAO) of the United Nations estimates that fisheries and aquaculture assure the livelihoods of 10 to 12 percent of the world’s population, with more than 90 percent of those employed by capture fisheries working in small-scale operations in developing countries. The potential to generate increasingly sizable environmental, social, and financial returns from the ocean can only be achieved if fisheries are managed in a sustainable and responsible manner. Understanding the concerns and needs of impact investors will allow development organizations, non-government organizations (NGOs), and others, to better design their interventions to encourage private sector participation while leveraging and preserving scarce public dollars for critical public investments. This paper provides an overview for international development organizations, development finance institutions, NGOs, and the governments they work with of: (i) the key concerns that impact investors may have when considering the financing of sustainable fisheries, and (ii) potential approaches for public-private partnerships to overcome these obstacles. It presents three models for sequencing and combining different sources of capital to overcome these obstacles: serial approach; consolidated approach; and parallel approach. Finding effective ways to combine public and private financing and coordinate interventions will help ensure that capture fisheries continue to provide long-term economic benefits and remain plentiful for the millions of people who depend on fish for food and livelihoods.